Pengaruh Good Corporate Governance Terhadap Kualitas Laba Perusahaan (Studi pada Perusahaan Sektor Consumer Goods dalam Bursa Efek Indonesia Periode 2016-2018) - Lisa J. C. Polimpung (Jurnal Akuntansi, 2020)
Financial statements reflect the state of the company where in a financial statement a person can get various kinds of information where one of them is profit. Before investors make an investment they will use information about earnings for their consideration. This causes earnings quality to be one of the most important aspects because it is used in evaluation materials to measure the performance of a company because investors expect quality earnings. Earnings quality is one of the driving factors used by investors before making investment decisions. This study wants to see whether the variables contained in good corporate governance which are divided into managerial ownership, institutional ownership, the size of the public accounting firm, audit committee and committee board have an influence on the quality of corporate earnings. This study conducted a study of companies listed on the Indonesia Stock Exchange in the period 2016-2018 where the number of observations was 60 observations and examined using the calculation of the coefficient of determination and multiple regression. The results found are managerial ownership and audit committee have an influence on earnings quality while other variables have no influence. Keywords: Good Corporate Governance, Earning Quality